2022
DOI: 10.1007/s10639-021-10867-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships Between English Teachers’ Lifelong Learning Tendencies with Professional Competencies and Technology Integrating Self-Efficacy

Abstract: The aim of this study is to examine the lifelong learning tendencies of English teachers, their professional competencies, and their self-efficacy in integrating technology. For this purpose, a descriptive survey model was used in this study. The participants of the research consist of 561 English teachers working in institutions (private and state) affiliated to the Ministry of National Education selected from every geographical region of Turkey. Participants work in primary, secondary, and secondary educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
2
10
0
1
Order By: Relevance
“…However, there is a significant difference between in-service teachers' digital competence, digital tools use, and ICT integration based on their age. The previous study also confirmed the same results [52,53]. Teachers aged 31-35 years have…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…However, there is a significant difference between in-service teachers' digital competence, digital tools use, and ICT integration based on their age. The previous study also confirmed the same results [52,53]. Teachers aged 31-35 years have…”
Section: Plos Onesupporting
confidence: 83%
“…Additionally, some studies suggested there is no difference between teachers’ age, gender, teaching experience, and self-efficacy during ICT integration [ 7 , 51 ]. However, some researchers verified the opposite result [ 52 , 53 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also found that researchers described lifelong learning abilities using terms such as “lifelong learning skills,” “lifelong learning competencies,” and “lifelong learning tendencies.” Some studies also investigated the impacts of demographic data to address their research problems (e.g., Buza et al, 2010 ; Nacaroglu et al, 2021 ; Sen & Durak, 2022 ; Shin & Jun, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various variables have been studied with regards to teachers' self-efficacy about technology integration, with the most common ones relate to demographics and experience, as a recent literature review suggests (Corry & Stella, 2018). Gender has shown mixed results, with some evidence suggesting for the advantage of men over women and of younger over older teachers (e.g., Šabić et al, 2022a), and some indicating no such associations (Şen & Yildiz Durak, 2022;e.g., Tweed, 2013). Experience-related variables have also shown mixed results; for example, experience of teaching with technology was sometimes found to be positively associated with selfefficacy (e.g., Baroudi & Shaya, 2022;Dolighan & Owen, 2021) and sometimes no associations were found (e.g., Tweed, 2013).…”
Section: Self-efficacy For Integrating Technology In Teachingmentioning
confidence: 99%